Evaluation of Aspartate Aminotransferase to Platelet Ratio Index as a Marker for Cirrhosis: A Study from Bir Hospital, Nepal - Lama, Ganesh; Yadav, Shree Narayan; Sahani, Bikash (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Liver cirrhosis is a leading cause of morbidity and mortality worldwide, including Nepal. Liver biopsy, the gold standard for fibrosis assessment, is invasive and carries various risks. The Aspartate Aminotransferase to Platelet Ratio Index (APRI) offers a non-invasive, cost-effective alternative. However, data on its utility in Nepalese populations are limited. Methods: This cross-sectional study enrolled 58 cirrhotic patients and 58 healthy controls at Bir Hospital from April 2019 to January 2020. Clinical examinations, laboratory tests, and ultrasonography were performed. APRI with a cut-off of 0.5 was evaluated using SPSS version 23, applying chi-square and ANOVA tests. Results: Among 116 participants, APRI at a 0.5 cut-off demonstrated 88.3% sensitivity, 82.5% specificity, 90.1% positive predictive value, and 70.2% negative predictive value (p = 0.002, 95% CI). Conclusion: APRI is a reliable non-invasive tool for diagnosing liver fibrosis in cirrhotic patients, offering high sensitivity and specificity. It is practical for bedside use, especially in resource-limited settings.